Physical and Mechanical Characteristics of Natural Adhesives in the Preparation of Composite Boards from Coconut Fiber as an Effort to Address Environmental Issues - Gahung, Mikhael Farly; Tooy, Dedie; Longdong, Ireine Adriana (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
This research aimed to develop coconut fiber boards using a mixture of cassava starch adhesive with a focus on examining the physical characteristics (density, moisture content, and thickness development) and mechanical properties (modulus of elasticity and modulus of rupture) of the composite boards made from coconut fiber using cassava starch adhesive with the addition of 25% citric acid. Additionally, the research evaluated the physical and mechanical characteristics of the fiberboards, following the guidelines of SNI 01-4449-2006 using an experimental method. The results showed that the fiberboards produced from coconut fiber and modified cassava starch adhesive (25% citric acid) exhibited specific physical characteristics. The density, moisture content, and thickness development ranged from 0.46 to 0.57 g/cm³, 13.18% to 14.39%, and 8.39% to 10.60% after two hours of soaking as well as 19.05% to 32.06% after 24 hours. Furthermore, the mechanical properties of the boards indicated a modulus of elasticity (MOE) and a modulus of rupture (MOR) ranging from 19247.33 to 42740.38 kg/cm² and 116.36 to 178.07 kg/cm², respectively. These findings are expected to provide valuable information for further research to obtain environmentally friendly adhesive materials. Keywords: Agriculture, Coconut fiberboard, Environmental friendly, Natural adhesive, Wood.